2012
DOI: 10.1021/jo300290v
|View full text |Cite
|
Sign up to set email alerts
|

Probing for a Leaving Group Effect on the Generation and Reactivity of Phenyl Cations

Abstract: Phenyl cations are smoothly generated by the photoheterolytic cleavage of an Ar-LG bond (LG = leaving group). With the aim of evaluating the scope of the method, a series of 4-methoxy-2-(trimethylsilyl)phenyl derivatives (sulfonic, LG = MeSO(3) and CF(3)SO(3), phosphate, LG = (EtO)(2)(O)PO esters and the corresponding chloride) have been compared as probes for evaluating the leaving group ability. The photocleavage was a general reaction, with the somewhat surprising order (EtO)(2)(O)PO ∼ Cl > CF(3)SO(3) > MeS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 53 publications
2
7
0
Order By: Relevance
“…A peculiar case is represented by 1g. As previously observed in related sulfonate esters (mesylates, triates), 16 the presence of a silicon-based substituent ortho to the sulfonate moiety signicantly increased the overall photoreactivity. 16 The same behaviour was found here, although the cleavage shied from heterolysis of an Ar-OS bond (in the cases of mesylate and triate) 16 to ArO-S homolysis (in the case of tosylate).…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…A peculiar case is represented by 1g. As previously observed in related sulfonate esters (mesylates, triates), 16 the presence of a silicon-based substituent ortho to the sulfonate moiety signicantly increased the overall photoreactivity. 16 The same behaviour was found here, although the cleavage shied from heterolysis of an Ar-OS bond (in the cases of mesylate and triate) 16 to ArO-S homolysis (in the case of tosylate).…”
Section: Discussionsupporting
confidence: 73%
“…As previously observed in related sulfonate esters (mesylates, triates), 16 the presence of a silicon-based substituent ortho to the sulfonate moiety signicantly increased the overall photoreactivity. 16 The same behaviour was found here, although the cleavage shied from heterolysis of an Ar-OS bond (in the cases of mesylate and triate) 16 to ArO-S homolysis (in the case of tosylate). The presence of oxygen promoted efficient trapping of the ArSO 2 c radical II (Scheme 2, path e), prior to recombination with the phenoxy radical, and PTSA was obtained via the corresponding arylperoxysulfonyl radical IV.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The reaction of 4-methoxy-2-(trimethylsilyl)benzene derivatives with acetonitrile/acetone/water was found to be dependent upon the leaving group (Scheme 52). 271 The electrochemical acetamidation of benzene, benzoic acid, ethyl benzoate, and acetophenone was carried out using acetonitrile and a platinum electrode; no yields were reported. 272 The proposed mechanism involves the formation of a radical cation, which is attacked by the acetonitrile nitrogen.…”
Section: Review Syn Thesismentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] Although the long-term aspiration of designing commercially interesting organic magnetic materials remains elusive, fundamental studies have identified several families of organic species that are either ground state triplets or have low-energy triplet states. [11][12][13][14][15][16][17][18] These include carbenes, [19][20][21] nitrenes, [22][23][24][25] diradicals, [1,[26][27][28][29][30][31][32] nitrenium ions, [33,34] certain aryl cations, [35][36][37][38][39] , and antiaromatic cations such as cyclopentadiene. [40,41] Recent computational and experimental studies in our laboratory have characterized several new types of ion-diradicals that also have low energy triplet states.…”
Section: Introductionmentioning
confidence: 99%